THE SYSTEMATIC REVIEW OF MANAGEMENT OF CATARACT SURGERY IN PATIENTS WITH DIABETES MELLITUS - Lianda, Felia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Diabetes mellitus (DM) is a chronic systemic disease whose prevalence has risen over time. Diabetes can impair all eye tissues, with cataracts being the most common complication. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 679 articles, whereas the results of our search on SCIENCE DIRECT brought up 338 articles. The results of the search conducted for the last year of 2014 yielded a total 49 articles for PubMed and 15 articles for SCIENCE DIRECT. In the end, we compiled a total of  5 papers, 3 of which came from PubMed and 2 of which came from SCIENCE DIRECT. We included five research that met the criteria. Conclusion: In summary, modern surgical and pharmacologic therapy may make diabetic patients' surgeries safer and more effective. This underlines the necessity of patient education prior to surgery.